Cutaneous Subacute Lupus with Chronic HCV Infection - Entela Shkodrani; Alert Xhaja; Silvan Frangaj; Amarda Cenko (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Background: Chronic hepatitis C remains a significant global health burden affecting a substantial number of individuals worldwide. Chronic infection with Hepatitis C Virus (HCV) is the leading cause of chronic hepatitis, cirrhosis, and liver cancer, and is the primary indication for liver transplantation. HCV can produce extrahepatic clinical manifestations and simulate autoimmune, rheumatologic and dermatologic diseases. Case Report: A 34-year-old female patient presented to the Dermatology Department of the University Hospital Centre "Mother Tereza” with a lingering cutaneous eruption accompanied by itching and burning. Clinical examination revealed malar facial rash and papulo-squamous lesions on the back, chest and upper limbs. The lab results show Positive Antinuclear Antibodies, Extracted Nuclear Antigens, and Cryoglobulins. The systemic corticosteroid therapy (Prednisolone 50mg) and interdisciplinary consultations (Nephrologist, Rheumatologist, Neurologist and Gastro-hepatologist) were initiated together for the patient. Conclusion: Chronic HCV infection may be associated with clinical extrahepatic manifestations, which can be interpreted incorrectly. This case reflects the ability of HCV to imitate a Cutaneous and Systemic Lupus Erythematosus that easily could have been wrongly diagnosed and mismanaged. Close cooperation between the relevant specialists in such a case is essential. HCV infection can be added to the list of possible differential diagnoses of an Acute/Subacute Cutaneous Lupus Erythematosus.